2020
DOI: 10.3390/ijerph17041322
|View full text |Cite
|
Sign up to set email alerts
|

HIV Testing and Risks of Sexual Behavior among HIV-Negative Men Who Have Sex with Men in Ningbo, China

Abstract: Human immunodeficiency virus (HIV) testing is confirmed as a preventive strategy for HIV control. However, the testing rate and risk behaviors of HIV-negative men who have sex with men (MSM) remain unclear. We aimed to examine factors associated with HIV testing and high-risk behaviors among HIV-negative MSM. From July 2016 to June 2017, participants were recruited by snowball sampling from WeChat groups, bars, and other venues. HIV testing was performed to exclude HIV-positive MSM. Face-to-face questionnaires… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
1
13
1
Order By: Relevance
“…However, several studies have shown that HIV testing among MSM is not as satisfactory as expected [ 30 , 31 ]. Based on the findings of HIV testing in Tianjin [ 32 ] and Ningbo [ 33 ], the testing rates were 69.95% (sample size = 4316) and 57.1% (sample size = 988), respectively, which were lower than our results. We have reason to believe that HIV testing is better among the MSM population in Western China.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…However, several studies have shown that HIV testing among MSM is not as satisfactory as expected [ 30 , 31 ]. Based on the findings of HIV testing in Tianjin [ 32 ] and Ningbo [ 33 ], the testing rates were 69.95% (sample size = 4316) and 57.1% (sample size = 988), respectively, which were lower than our results. We have reason to believe that HIV testing is better among the MSM population in Western China.…”
Section: Discussioncontrasting
confidence: 94%
“…But the MSM population is a marginal population that is difficult to reach, and we had to use such a sampling method. Similarly, many studies of factors influencing HIV testing in MSM population have encountered the same problem [ 32 , 33 ]. (2) As a sensitive group, MSM pay great attention to privacy issues.…”
Section: Discussionmentioning
confidence: 99%
“…11 According to a cross-sectional study among Chinese MSM in Ningbo, China (in 2017), the estimated proportion of HIV testing in last year was only 57.1%. 12 According to another systematic review and meta-analysis focused on HIV testing among Chinese MSM, no more than 50% of Chinese MSM reported having ever been tested for HIV, and only 38% Chinese MSM reported being tested in the past year. 13 Health-related theories 14,15 have proven that health behavior, such as access to HIV testing services, not only depended on intrapersonal influences but also are influenced by social and environmental factors, or structural level factors.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Chinese MSM often marry a woman to conceal their homosexuality [ 28 ]. Being married might be an indicator of more risky behaviors or taking responsibility of family [ 29 ]. In addition, we found participants with increased quality of sleep were more likely to get HIV test.…”
Section: Discussionmentioning
confidence: 99%